Satisfaction With Medication Therapy Management Services at a University Ambulatory Care Clinic. (June 2016) - Kim, Shiyun; Martin, Michelle T.; Pierce, Andrea L.; Zueger, Patrick
A survey was issued to patients enrolled in the Medication Therapy Management Clinic (MTMC) at University of Illinois Hospital and Health Sciences (June 2011-January 2012) in order to assess satisfaction with pharmacy services provided by pharmacists. A 23-item survey was offered to 65 patients in the MTMC program before or after clinic visits. Since there is a paucity of data indicating the level of satisfaction with MTM services provided by pharmacists, this survey may contribute to the process of building a greater collaboration between the pharmacist and patient. Sixty-two of 65 patients completed the survey; satisfaction with MTMC pharmacists was demonstrated to be significantly positively correlated with overall satisfaction with the MTMC. Patient satisfaction is not significantly different according to age, gender, ethnicity, or number of disease states. Satisfaction with the pillbox service is not significantly different between younger and older patients. It was also noted that patients taking a greater number of medications had higher levels of satisfaction. Most patients indicated that they were satisfied with the MTMC pharmacists and services; further study linking patient satisfaction with MTM services to improved patient outcomes may allow our MTMC to serve as a model for other pharmacist-managed MTMCs serving similar patient populations.